Pembuatan Silase Domba Dengan Memanfaatkan Fermentasi Mikroorganisme Menggunakan Produk M-Bio - Yunianto, Agus; Femi Nurul Fauzi; Firmasyah, Irvan; Fahlevi, Reza; Mutolib, Abdul; Djuliansah, Dedi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Inovatif, 2024)
The problem faced by sheep farmers is the limitation of the number of sheep feeds in the farm, as well as the lack of nutritional additions to the feed. The dedication is aimed at producing alternative feed solutions using greening technology using local feed ingredients, with fermentation processes and using microorganisms found in M-Bio products. (silase). The dedication activities are carried out through the community dedication scheme in the livestock group Berkah Waringkas Farm, Ciharalanag Village, Cijeungjing District, Ciamis District in December 2023. The dedication activities include five methods: socio-reflective methods, early study method, socialization method, simulation of silas making, and evaluation and support. The dedication activities focused on making silas using local raw materials surrounding the fermentation process, as well as farmers better understanding the concept of adding nutrients to feed for sheep's fattening. Based on the results of the activity showed that the participants who were present looked enthusiastic in following the material exhibition and active in answering questions about the benefits of the use of silas, as well as the process of feeding the cattle. Activity evaluation questionnaire results show that this socialization activity has a good assessment for the participants